The Dual Role of Zinc in Spinach Metabolism: Beneficial × Toxic - Veronika Zemanová; Daniela Pavlíková; Milan Novák; František Hnilička (Plants)
The effects of zinc (Zn) on the physiology of spinach (Spinacia oleracea L.) were investigated in a pot experiment with increasing Zn contents in the horticultural substrate (0, 75, 150, and 300 mg Zn kg−1). Interactions among nutrients in the substrate solution affected plant vitality, biomass yield, and nutrient content in plants. The water-soluble Zn fraction increased with the Zn dose, rising from 0.26 mg kg−1 in the Control to 0.98 mg kg−1 in the Zn300 treatment. The most pronounced effects of elevated Zn content were observed for Ca, Mg, and Mn. In spinach, the dual role of Zn was evident through its impact on yield, particularly regarding aboveground biomass. The positive effects of Zn doses up to 150 mg kg−1 were supported by the tolerance index (TI). In contrast, the 300 mg kg−1 Zn dose exhibited toxic effects, resulting in a 33.3% decrease in the yield of aboveground biomass and a TI value of 0.7. The effects of Zn on nutrient content in aboveground biomass varied with the dose, and the relationship between Zn and P, Fe, Mn, Ca, and K content confirmed a correlation. The toxic effect of the Zn300 treatment was evidenced by a decrease in Ca, Cu, and Fe contents. Additionally, the results of the Zn300 treatment indicated a negative effect on the synthesis of photosynthetic pigments and photosynthesis, likely due to induced oxidative stress. The production of oxalic acid also suggested a toxic effect of the highest Zn dose on spinach.